Peran Kepala Sekolah dalam Pengembangan Kewirausahaan di SMK Negeri 1 Sedan - Triyastuti, Novitasari; Lilik Herawati; Soedjono (CV. Ulil Albab Corp, 2024)
This study aims to analyze the role of the school principal in developing entrepreneurship at SMK Negeri 1 Sedan. Using a qualitative method, data were collected through observations, interviews, and documentation, then analyzed descriptively. The results of the study show that the school principal acts as an effective managerial leader in managing school resources through strategic planning, organizing, and evaluating entrepreneurship programs. In addition, the principal also strengthens partnerships with the business and industry sector (DUDI) and optimizes independent school enterprises. However, challenges such as limited human resources, facilities, capital, and competition with other business players have emerged. This study emphasizes that while the principal has played a significant role, additional strategies are needed to overcome the challenges in developing entrepreneurship at SMK Negeri 1 Sedan.